Relationship between H. Pylori Patients and Autoimmune Thyroid Disease - Marwah Ali Oudah (Institute of Medico-legal Publications Pvt Ltd, 2020)
Autoimmune Thyroid Disease (AITD) Autoimmune Thyroid Disease is one of the diseases, more common in women than men, caused by a combination of reasons discussed later. In this study, we have tried to understand how Autoimmune Thyroid Disease is related to H. pylori or Helicobacter Pylori. We have discussed the pathology and the manner in which AITD is developed This report depicts the relationship between Helicobacter pylori (H. pylori) and Autoimmune Thyroid Disease or Autoimmune Thyroiditis. However, some other reports concerning the relationship between H. pylori infection and Autoimmune Thyroiditis are conflicting. We’ve discussed how AITD is developed, along with the causes and effects of the disease. In this study, we’ve also aimed at determining the presence of H. pylori bacteria in AITD patients, particularly in Hashimoto’s Thyroiditis and Grave’s disease two of the commonly occurring thyroid diseases. The manner in which AITD develops is multi-factorial and H. pylori infection is reported more in AITD patients (adults). H. pylori is said to be involved usually in non gastrointestinal conditions.